THE EFFECTIVENESS OF GUIDANCE AND COUNSELING INTERVENTIONS IN IMPROVING STUDENTS’ ACADEMIC RESILIENCE: A SYSTEMATIC LITERATURE REVIEW - Widia, Amanda Putri; Bustomi, Yazid Imam (International Journal of Multidisciplinary Reseach, 2025)
This study examines the effectiveness of guidance and counselling (GC) interventions in enhancing academic resilience among students. Academic resilience enables individuals to adapt to and overcome educational challenges; however, a comprehensive review of GC’s role in this development is lacking. Using a systematic review following PRISMA guidelines, the study searched reputable databases, including Scopus, Web of Science, Google Scholar, and DOAJ, for empirical studies published within the last 10 years. The inclusion criteria focused on studies involving GC interventions across various educational levels that measured academic resilience. The extracted data covered intervention types, duration, target population, resilience tools, and outcomes. The review found that both individual and group GC interventions effectively improve dimensions of academic resilience, including self-regulation, optimism, self-efficacy, and failure resilience. Interventions emphasizing coping skills, social support, and cognitive restructuring showed significant positive effects. The study highlights the vital role of counsellors in designing GC programs to strengthen academic resilience, offering insights for developing GC curricula, and guiding education practitioners and policymakers